A pneu choice - Lee, Nerissa Zhi Ying (2018)
A Pneu Choice is a pilot campaign on pneumococcal vaccinations for the elderly organised by four final-year undergraduates from the Wee Kim Wee School of Communication & Information, Nanyang Technological University. It aimed to persuade elderly in the Queenstown and Bukit Merah planning areas, via knowledge gain and attitudinal change, to take the pneumonia vaccine. Street surveys and in-depth interviews were used to assess knowledge levels and attitudes of the elderly towards pneumonia and pneumococcal vaccines. These showed that the elderly possessed an illusion of unique invulnerability and low knowledge levels of the disease and its vaccines. Message testing also demonstrated the elderly’s preference for gain-framed messages, as well as traditional media and face-to-face interactions, all of which became the predominant campaign communication channels used. Campaign evaluation found that positive attitudes towards the vaccinations in elderly played a key role in driving their adoption of the one-off health behaviour of getting the PCV13. In addition, direct engagement with influential authoritative figures such as doctors enhances persuasion efforts. The campaign reached over 2,700 elderly. It culminated with a vaccination drive providing pneumococcal vaccinations to 84 interested elderly, with additional vaccination efforts extending beyond the campaign to 211 more.